Glotto-politics approach to politic-linguistic of bilingualism in Colombia - Miranda Montenegro, Iván Ricardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
This paper seeks to fulfill an analytical revision in some documents related to policies of bilingualism in order to determine conceptual and methodological trends regarding the insertion of the English language into the Colombian educational system. To this purpose, some research reports carried out in diverse geopolitical contexts were analyzed so as to obtain a wide-ranging view of the current socio-linguistic phenomenon of insertion of this international language. The analysis shows a clear tendency to consider both the legislative enactments and implementation decisions of bilingualism as politic-linguistic strategies that occur within a frame of a capitalist ideology that looks for the training of individuals in basic competences that favors the global market.